The Influence of Corporate Social Responsibility and Financial Reporting Aggressiveness on Tax Aggressiveness with Corporate Environmental Performance as a Moderating Variable - Lestary, Annisa Ayu (Maksi, 2023)
This study aims to examine the influence of corporate social responsibility (CSR) and financial reporting aggressiveness on tax aggressiveness, using corporate environmental performance as a moderating variable. This research utilizes quantitative analysis with descriptive associative statistics. Hypothesis testing is conducted using multiple linear regression with a sample of 50 companies participating in PROPER in the Basic Materials and Energy sectors listed on the Indonesia Stock Exchange. The results of the study indicate that CSR and financial reporting aggressiveness do not have a significant influence on tax aggressiveness, both partially and simultaneously. Furthermore, corporate environmental performance is unable to moderate the relationship between CSR and tax aggressiveness.